2022
DOI: 10.1186/s12871-022-01582-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk stomach in laboring women allowed to unrestrictive oral intake: a comparative cross-sectional study

Abstract: Background Although restricting food intake during labor is recommended by guidelines, intrapartum starvation has not been popular in some regions. We conducted this comparative cross-sectional study to determine the prevalence of risk stomach in non-fasted laboring women compared with fasted non-laboring women using gastric ultrasound. Methods Ultrasound examination of the antrum was performed in 50 term fasted non-laboring women before elective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…US assessment of gastric contents in the labouring patient is more difficult and subjected to more variable factors [33]. Yet again, studies have confirmed that labouring patients are more likely to have slower gastric emptying and eating during labour may contribute to larger volumes of gastric residues [34,35]. There is emerging evidence that epidural analgesia, including opiates, may not contribute to delayed gastric emptying during labour any more than labour itself [34,36].…”
Section: Aspiration Risk In Pregnancymentioning
confidence: 99%
“…US assessment of gastric contents in the labouring patient is more difficult and subjected to more variable factors [33]. Yet again, studies have confirmed that labouring patients are more likely to have slower gastric emptying and eating during labour may contribute to larger volumes of gastric residues [34,35]. There is emerging evidence that epidural analgesia, including opiates, may not contribute to delayed gastric emptying during labour any more than labour itself [34,36].…”
Section: Aspiration Risk In Pregnancymentioning
confidence: 99%